Method for preparing composite solid electrolyte based on polymerization inhibitor adsorption carrier with nanostructure
By using nanostructured polymerization resist adsorption carrier technology in composite electrolytes, the problems of poor repeatability of composite electrolytes and electrochemical cycling performance are solved, the high performance and stability of composite solid electrolytes are achieved, and the overall lithium-ion battery is improved. performance.
Patent Information
- Application Number
- CN202411593261.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing composite electrolytes have problems with poor experimental repeatability and electrochemical cycling performance, which affect the stability and performance of lithium-ion batteries.
The composite solid electrolyte is prepared by using a polymerization inhibitor adsorption carrier based on nanostructure. By mixing the inorganic nanofiller with the polymerization inhibitor and mixing it with polymerized monomer, initiator, lithium salt and organic solvent, the in situ cured electrolyte precursor is obtained. The body is then cured under specific conditions to form a composite solid electrolyte.
The wetting property, polymerization reaction uniformity and ionic conductivity of the composite solid electrolyte are improved, and the stability, magnification and cycling performance of semi-solid lithium-ion batteries are enhanced.
Smart Images

Figure BDA0005126135250000101
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a method for preparing a composite solid electrolyte based on a nanostructured inhibitor adsorption carrier. Background Art
[0002] Lithium-ion batteries are widely used in digital products and new energy vehicles due to their high energy density and low self-discharge characteristics. However, the energy density of traditional organic liquid electrolytes has reached a bottleneck, and in extreme cases, they are prone to fire and explosion accidents, limiting the commercial application of large-capacity and high-energy lithium secondary batteries. Therefore, it is crucial to improve the safety and electrochemical performance of lithium-ion batteries, especially to design and develop high-performance electrolytes.
[0003] Solid-state electrolytes have significant safety advantages over traditional organic electrolytes because they can reduce the flammable components in the battery. However, solid-state electrolytes also face problems such as large solid-solid interface impedance and low ionic conductivity, which affect the battery's charge and discharge performance and rate performance. Polymer solid electrolytes can significantly improve the safety and cycle performance of lithium-ion batteries due to their good flexibility and excellent interface contact properties. However, at room temperature, the low ionic conductivity of polymer solid electrolytes limits their industrial application.
[0004] To solve these problems, researchers usually use organic / inorganic composite solid electrolytes to improve the interfacial contact and ionic conductivity of solid-state batteries. Inorganic nanostructured solid electrolyte materials and inorganic inert fillers are two commonly used additives that can significantly improve the performance of composite electrolytes. However, due to the phase separation between ceramic fillers and polymers and the high surface energy of the ceramic fillers themselves, large particles of ceramic fillers are prone to agglomeration in the polymer matrix, resulting in the waste of some scarce elements, poor experimental repeatability of composite electrolytes, and reduced electrochemical cycling performance. Therefore, it is necessary to develop a nanostructured inhibitor adsorption carrier to prepare a composite solid electrolyte. Summary of the invention
[0005] The present application provides a method for preparing a composite solid electrolyte based on a nanostructured inhibitor adsorption carrier to solve the problems of poor experimental repeatability and electrochemical cycle performance of existing composite electrolytes, and achieves that the prepared composite solid electrolyte has the characteristics of good wettability, uniform polymerization reaction, high ion conductivity, etc. when used in lithium-ion batteries, and can improve the stability, rate and cycle performance of semi-solid lithium-ion batteries.
[0006] The present application provides a composite solid electrolyte prepared by a nanostructured inhibitor adsorption carrier. The raw material components for preparing the composite solid electrolyte include, by weight, 10-20 parts of a small molecule polymerization monomer, 1-3 parts of an initiator, 2-6 parts of a lithium salt, 2-8 parts of a filler, 1-4 parts of an inhibitor, and 5-10 parts of an organic solvent.
[0007] Preferably, the small molecule polymer monomer includes any one or a combination of at least two of acrylic acid, methacrylic acid, methyl methacrylate, pentaerythritol tetraacrylate, pentaerythritol triacrylate, acrylonitrile, ethylene carbonate, ethylene oxide or 1,3-dioxolane.
[0008] Preferably, the initiator includes any one of azobisisobutyronitrile, azobisisoheptanenitrile, azoisobutylcyanoformamide, dimethyl azobisisobutyrate, dicumyl peroxide or dibenzoyl peroxide, or a combination of at least two thereof.
[0009] Preferably, the lithium salt includes any one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(difluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium bis(oxalatoborate), lithium difluorooxalatoborate or lithium bis(oxalatoborate), or a combination of at least two thereof.
[0010] Preferably, the filler includes a first filler and a second filler, the particle size of the first filler is 10nm-500nm; the first filler includes at least one of Al2O3, TiO2, SiO2, ZrO2, Ta2O5, La2O3; the particle size of the second filler is 300-1000nm; the second filler includes at least one of Li0.75La0.5TiO3, Li1.3Al0.3Ti1.7(PO4)3, Li7La3Zr2O12, Li10GeP2S12.
[0011] Preferably, the polymerization inhibitor includes any one of hydroquinone, p-hydroxyanisole, 2,6-di-tert-butyl-p-cresol, 2,5-di-tert-butyl-hydroquinone, 2-tert-butyl-hydroquinone, p-benzoquinone, methylhydroquinone or tetrachlorobenzoquinone, or a combination of at least two thereof.
[0012] Preferably, the organic solvent includes any one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl formate, dimethoxymethane or acetonitrile, or a combination of at least two thereof.
[0013] Preferably, the raw material for preparing the composite solid electrolyte further includes 2-5 parts of an additive, wherein the additive includes any one or a combination of at least two of vinylene carbonate, fluoroethylene carbonate, propylene sulfite, ethylene sulfate, fluorobenzene or sodium dodecyl sulfate.
[0014] Preferably, a method for preparing a composite solid electrolyte based on a nanostructured inhibitor adsorption carrier comprises the following steps:
[0015] A. Firstly, an inorganic nanofiller and a polymerization inhibitor are mixed, and then a polymerization monomer, an initiator, a lithium salt, and an organic solvent are added and mixed to obtain an in-situ solidified electrolyte precursor;
[0016] B. Then, the in-situ solidified electrolyte precursor is injected into the battery cell, and allowed to stand for 1 minute under a vacuum of -80 kPa. After vacuum packaging, it is allowed to stand for 12-48 hours in an environment of 20-35°C. The pressure during curing is 0.6-3 MPa, and it is cured at 45-80°C for 4-12 hours to obtain an in-situ solidified composite solid electrolyte.
[0017] Preferably, based on the total mass of the in-situ solidified electrolyte precursor as 100%, the mass percentage of the polymerized monomer is 1%-40%, the mass percentage of the initiator to the mass percentage of the polymerized monomer is 0.01%-3%, the concentration of the lithium salt in the in-situ solidified electrolyte precursor is 1-3 mol / L, the mass percentage of the inhibitor to the mass percentage of the polymerized monomer is 0.0005%-10%, the mass percentage of the organic solvent is 60%-90%; and the mass percentage of the additive is 0-10%.
[0018] Beneficial effects:
[0019] (1) The preparation method of the present invention is simple. When the composite solid electrolyte is used in lithium-ion batteries, it has the characteristics of good wettability, uniform polymerization reaction, high ion conductivity, etc., and can improve the stability, rate and cycle performance of semi-solid lithium-ion batteries.
[0020] (2) In the present invention, in order to improve the dispersibility of ceramic fillers in the polymer matrix, we can effectively prevent the agglomeration of nanofillers by adsorbing inhibitors on the nanofillers to improve their dispersibility and interfacial compatibility in the polymer matrix, and at the same time improve the thermal stability of the composite electrolyte. At the same time, the inhibitors adsorbed on the surface of the nanofillers can produce an induction period to delay the polymerization time of the polymerized monomers. After the in-situ curing precursor liquid is fully infiltrated in the lithium-ion battery, the curing reaction is carried out, and a uniformly cured in-situ cured composite solid electrolyte can be formed.
[0021] (3) In the present invention, the first filler added to the raw materials for preparing the in-situ solidified composite solid electrolyte, the inorganic nanofiller, on the one hand, reduces the crystallinity of the polymer after the polymerization reaction, and enhances the chain segment mobility of the polymer, which is beneficial to the transmission of lithium ions, thereby improving the ionic conductivity of the solid electrolyte. On the other hand, the inorganic nanofiller can serve as a polymerization reaction center, which is beneficial to the formation of a uniform polymerization reaction after being uniformly diffused and distributed in the positive electrode plate, thereby forming a solidified uniform solid electrolyte. In addition, the inorganic nanofiller contacts with the active material, and lithium ions diffuse to the interface to form a fast ion layer, which is beneficial to improving the ionic conductivity while protecting the side reactions of the positive electrode material and the residual electrolyte, improving and enhancing the stability of the material, and improving the cycle performance of the battery.
[0022] (4) In the present invention, the second filler added to the raw materials for preparing the in-situ solidified composite solid electrolyte, the micro-nano solid electrolyte filling, on the one hand, acts as a lithium ion fast conductor to provide high ion conductivity; on the other hand, the micro-nano solid electrolyte material forms a close contact with the active material and the polymer electrolyte interface, thereby reducing the impedance of the semi-solid lithium ion battery and improving the performance of the battery; at the same time, the micro-nano solid electrolyte is in close contact with the active material, diffuses on the surface of the active material during the electrochemical reaction to form a protective layer, stabilizes the structure of the active material and thereby improves the cycle performance of the battery.
[0023] The above description is only an overview of the technical solution of the embodiment of the present application. In order to more clearly understand the technical means of the embodiment of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the embodiment of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used in the specification of the application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0026] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase "embodiments" in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0027] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application is clearly and completely described below.
[0028] The present application provides a composite solid electrolyte prepared by a nanostructured inhibitor adsorption carrier. The raw material components for preparing the composite solid electrolyte include, by weight, 10-20 parts of a small molecule polymerization monomer, 1-3 parts of an initiator, 2-6 parts of a lithium salt, 2-8 parts of a filler, 1-4 parts of an inhibitor, and 5-10 parts of an organic solvent.
[0029] Embodiment 1:
[0030] The raw material components for preparing the composite solid electrolyte include 10 parts of small molecule polymerization monomers, 1 part of initiator, 2 parts of lithium salt, 2 parts of filler, 1 part of inhibitor and 5 parts of organic solvent in parts by weight.
[0031] In this embodiment, the small molecule polymer monomer includes a mixture of pentaerythritol tetraacrylate and pentaerythritol triacrylate.
[0032] In this embodiment, the initiator includes a mixture of azobisisobutyronitrile and azobisisoheptanenitrile.
[0033] In this embodiment, the lithium salt includes a mixture of lithium hexafluorophosphate and lithium tetrafluoroborate.
[0034] In this embodiment, the filler includes a first filler and a second filler, the particle size of the first filler is 10 nm; the first filler includes a mixture of Al2O3 and TiO2; the particle size of the second filler is 300 nm; the second filler includes Li0.75La0.5TiO3.
[0035] In this embodiment, the polymerization inhibitor includes a mixture of hydroquinone and p-hydroxyanisole.
[0036] In this embodiment, the organic solvent includes a mixture of ethylene carbonate and propylene carbonate.
[0037] In this embodiment, the raw materials for preparing the composite solid electrolyte further include 2 parts of additives, and the additives include a mixture of vinylene carbonate and fluoroethylene carbonate.
[0038] In this embodiment, a method for preparing a composite solid electrolyte based on a nanostructured inhibitor adsorption carrier comprises the following steps:
[0039] A. Firstly, an inorganic nanofiller and a polymerization inhibitor are mixed, and then a polymerization monomer, an initiator, a lithium salt, and an organic solvent are added and mixed to obtain an in-situ solidified electrolyte precursor;
[0040] B. Then, the in-situ curing electrolyte precursor is injected into the battery cell, and it is allowed to stand for 1 minute under a vacuum of -80 kPa. After vacuum packaging, it is allowed to stand for 12 hours in an environment of 20°C. The pressure during curing is 0.6 MPa, and it is cured at 45°C for 4 hours to obtain an in-situ curing composite solid electrolyte.
[0041] In this embodiment, taking the total mass of the in-situ solidifying electrolyte precursor as 100%, the mass percentage of the polymerized monomer is 10%, the mass percentage of the initiator to the mass percentage of the polymerized monomer is 1%, the concentration of the lithium salt in the in-situ solidifying electrolyte precursor is 1 mol / L, the mass percentage of the inhibitor to the mass percentage of the polymerized monomer is 1%, the mass percentage of the organic solvent is 86%; and the mass percentage of the additive is 2%.
[0042] Embodiment 2:
[0043] The raw material components for preparing the composite solid electrolyte include 20 parts of small molecule polymerization monomers, 3 parts of initiators, 6 parts of lithium salts, 8 parts of fillers, 4 parts of inhibitors and 10 parts of organic solvents in parts by weight.
[0044] In this embodiment, the small molecule polymer monomer includes a mixture of pentaerythritol tetraacrylate, pentaerythritol triacrylate and acrylonitrile.
[0045] In this embodiment, the initiator includes a mixture of azoisobutylcyanoformamide and dimethyl azobisisobutyrate.
[0046] In this embodiment, the lithium salt includes a mixture of lithium perchlorate and lithium bis(difluorosulfonyl)imide.
[0047] In this embodiment, the filler includes a first filler and a second filler, the particle size of the first filler is 500nm; the first filler includes a mixture of SiO2 and ZrO2; the particle size of the second filler is 1000nm; the second filler includes Li1.3Al0.3Ti1.7(PO4)3.
[0048] In this embodiment, the polymerization inhibitor includes a mixture of 2,6-di-tert-butyl-p-cresol and 2,5-di-tert-butyl-hydroquinone.
[0049] In this embodiment, the organic solvent includes a mixture of dimethyl carbonate and diethyl carbonate.
[0050] In this embodiment, the raw material for preparing the composite solid electrolyte further includes 5 parts of an additive, wherein the additive includes a mixture of propylene sulfite and ethylene sulfate.
[0051] In this embodiment, a method for preparing a composite solid electrolyte based on a nanostructured inhibitor adsorption carrier comprises the following steps:
[0052] A. Firstly, an inorganic nanofiller and a polymerization inhibitor are mixed, and then a polymerization monomer, an initiator, a lithium salt, and an organic solvent are added and mixed to obtain an in-situ solidified electrolyte precursor;
[0053] B. Then, the in-situ curing electrolyte precursor is injected into the battery cell, and it is allowed to stand for 1 minute under a vacuum of -80 kPa. After vacuum packaging, it is allowed to stand for 14 hours in a 35°C environment. The pressure during curing is 3 MPa, and it is cured at 75°C for 5 hours to obtain an in-situ curing composite solid electrolyte.
[0054] In this embodiment, taking the total mass of the in-situ solidifying electrolyte precursor as 100%, the mass percentage of the polymerized monomer is 15%, the mass percentage of the initiator to the mass percentage of the polymerized monomer is 3%, the concentration of the lithium salt in the in-situ solidifying electrolyte precursor is 3 mol / L, the mass percentage of the inhibitor to the mass percentage of the polymerized monomer is 10%, the mass percentage of the organic solvent is 62%; and the mass percentage of the additive is 10%.
[0055] Embodiment three:
[0056] The raw material components for preparing the composite solid electrolyte include 12 parts of small molecule polymerization monomers, 2 parts of initiators, 3 parts of lithium salts, 7 parts of fillers, 3 parts of inhibitors and 7 parts of organic solvents in parts by weight.
[0057] In this embodiment, the small molecule polymer monomer includes a mixture of pentaerythritol tetraacrylate, pentaerythritol triacrylate, and ethylene oxide.
[0058] In this embodiment, the initiator includes a mixture of dicumyl peroxide and dibenzoyl peroxide.
[0059] In this embodiment, the lithium salt includes a mixture of lithium bis(oxalatoborate) and lithium difluorooxalatoborate.
[0060] In this embodiment, the filler includes a first filler and a second filler, the particle size of the first filler is 100 nm; the first filler includes a mixture of Ta2O5 and La2O3; the particle size of the second filler is 400 nm; the second filler includes Li7La3Zr2O12.
[0061] In this embodiment, the polymerization inhibitor includes a mixture of p-benzoquinone and methylhydroquinone.
[0062] In this embodiment, the organic solvent includes a mixture of methyl formate and dimethoxymethane.
[0063] In this embodiment, the raw materials for preparing the composite solid electrolyte further include 3 parts of additives, and the additives include a mixture of vinylene carbonate and ethylene sulfate.
[0064] In this embodiment, a method for preparing a composite solid electrolyte based on a nanostructured inhibitor adsorption carrier comprises the following steps:
[0065] A. Firstly, an inorganic nanofiller and a polymerization inhibitor are mixed, and then a polymerization monomer, an initiator, a lithium salt, and an organic solvent are added and mixed to obtain an in-situ solidified electrolyte precursor;
[0066] B. Then, the in-situ curing electrolyte precursor is injected into the battery cell, and it is allowed to stand for 1 minute under a vacuum of -80 kPa. After vacuum packaging, it is allowed to stand for 20 hours in an environment of 25°C. The pressure during curing is 1 MPa, and it is cured at 55°C for 7 hours to obtain an in-situ curing composite solid electrolyte.
[0067] In this embodiment, taking the total mass of the in-situ solidifying electrolyte precursor as 100%, the mass percentage of the polymerized monomer is 20%, the mass percentage of the initiator to the mass percentage of the polymerized monomer is 1%, the concentration of lithium salt in the in-situ solidifying electrolyte precursor is 2 mol / L, the mass percentage of the inhibitor to the mass percentage of the polymerized monomer is 5%, the mass percentage of the organic solvent is 71%; and the mass percentage of the additive is 3%.
[0068] Embodiment 4:
[0069] The raw material components for preparing the composite solid electrolyte include 15 parts of small molecule polymerization monomers, 2 parts of initiators, 4 parts of lithium salts, 5 parts of fillers, 3 parts of inhibitors and 8 parts of organic solvents in parts by weight.
[0070] In this embodiment, the small molecule polymer monomer includes a mixture of pentaerythritol tetraacrylate and pentaerythritol triacrylate.
[0071] In this embodiment, the initiator includes a mixture of azobisisoheptanonitrile, azoisobutylcyanoformamide, and dicumyl peroxide.
[0072] In this embodiment, the lithium salt includes lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, and a mixture of lithium bis(difluorosulfonyl)imide.
[0073] In this embodiment, the filler includes a first filler and a second filler, the particle size of the first filler is 300nm; the first filler includes a mixture of Al2O3, TiO2, SiO2, and ZrO2; the particle size of the second filler is 600nm; the second filler includes a mixture of Li0.75La0.5TiO3, Li1.3Al0.3Ti1.7(PO4)3, and Li7La3Zr2O12.
[0074] In this embodiment, the polymerization inhibitor includes a mixture of hydroquinone, p-hydroxyanisole, 2,6-di-tert-butyl-p-cresol, and 2,5-di-tert-butylhydroquinone.
[0075] In this embodiment, the organic solvent includes a mixture of ethylene carbonate, propylene carbonate, dimethyl carbonate, and diethyl carbonate.
[0076] In this embodiment, the raw materials for preparing the composite solid electrolyte further include 4 parts of additives, and the additives include a mixture of vinylene carbonate, fluoroethylene carbonate, propylene sulfite, and ethylene sulfate.
[0077] In this embodiment, a method for preparing a composite solid electrolyte based on a nanostructured inhibitor adsorption carrier comprises the following steps:
[0078] A. Firstly, an inorganic nanofiller and a polymerization inhibitor are mixed, and then a polymerization monomer, an initiator, a lithium salt, and an organic solvent are added and mixed to obtain an in-situ solidified electrolyte precursor;
[0079] B. Then, the in-situ solidified electrolyte precursor is injected into the battery cell, and allowed to stand for 1 minute under a vacuum of -80 kPa. After vacuum packaging, it is allowed to stand for 24 hours in an environment of 30°C. The pressure during curing is 2 MPa, and it is cured at 60°C for 8 hours to obtain an in-situ solidified composite solid electrolyte.
[0080] In this embodiment, taking the total mass of the in-situ solidifying electrolyte precursor as 100%, the mass percentage of the polymerized monomer is 20%, the mass percentage of the initiator to the mass percentage of the polymerized monomer is 2%, the concentration of the lithium salt in the in-situ solidifying electrolyte precursor is 2 mol / L, the mass percentage of the inhibitor to the mass percentage of the polymerized monomer is 5%, the mass percentage of the organic solvent is 68%; and the mass percentage of the additive is 5%.
[0081] In the present invention, the nanostructure as a carrier of the inhibitor helps to inhibit the polymerization reaction from proceeding too quickly and control the nucleation and growth of the polymer. This can reduce the coagulation of the polymer and improve the uniformity and stability of the electrolyte after curing. The two-dimensional structure of the nanosheet allows the distribution of the inhibitor to be more uniform, thereby effectively inhibiting the non-uniformity of the polymerization reaction. The nanosheet material forms a sheet network structure in the electrolyte, which helps to improve the mechanical properties and ion conductivity of the electrolyte. The high surface area of the nanotube and its hollow structure can effectively prolong the release time of the inhibitor and play a slow-release effect. This slow-release characteristic can better control the reaction rate in in-situ curing, avoid rapid cross-linking of the polymer, and improve the uniformity of the cured layer. The pore structure of the nano-mesoporous material can adsorb or anchor the inhibitor molecules in the pores, providing an effective confined space environment. This structure allows the inhibitor to be released more slowly in a confined space, thereby controlling the curing rate. Hierarchical micro-nano materials, because they have both micron- and nano-scale structures, can provide abundant adsorption sites at different structural levels. This multi-level structure can provide multi-level adsorption and sustained-release effects, which not only controls the distribution of inhibitors, but also provides diversified channels for the transmission of lithium ions. The above nanostructures are divided into different types, including nano-element materials (nanoparticles, hollow nanospheres, nanosheets, nanowires, nanotubes), nano-mesoporous materials and hierarchical micro-nano materials. Each structure has unique morphology and characteristics.
[0082] Experimental example:
[0083] The composite solid electrolytes prepared in various embodiments of the present invention were used for performance testing, and the data obtained are shown in the following table:
[0084]
[0085] In the present invention, in order to improve the dispersibility of ceramic fillers in polymer substrates, we can effectively prevent the agglomeration of nanofillers by adsorbing polymerization inhibitors on the nanofillers for surface modification, thereby improving their dispersibility and interfacial compatibility in the polymer substrate and improving the thermal stability of the composite electrolyte. At the same time, the polymerization inhibitor adsorbed on the surface of the nanofillers can produce an induction period to delay the polymerization time of the polymerization monomer, and the in-situ curing precursor liquid will undergo a curing reaction after being fully infiltrated in the lithium-ion battery, thereby forming a uniformly cured in-situ cured composite solid electrolyte.
[0086] In the present invention, the first filler added to the raw materials for preparing the in-situ cured composite solid electrolyte, the inorganic nanofiller, on the one hand, reduces the crystallinity of the polymer after the polymerization reaction, and enhances the segment mobility of the polymer, which is beneficial to the transmission of lithium ions, thereby improving the ionic conductivity of the solid electrolyte. On the other hand, the inorganic nanofiller can serve as a polymerization reaction center, which is beneficial to the formation of a uniform polymerization reaction after uniform diffusion and distribution in the positive electrode sheet, thereby forming a solidified uniform solid electrolyte. In addition, the inorganic nanofiller contacts with the active material, and lithium ions diffuse to the interface to form a fast ion layer, which is beneficial to improving the ionic conductivity while protecting the side reaction of the positive electrode material and the residual electrolyte, improving and enhancing the stability of the material, and improving the cycle performance of the battery.
[0087] In the present invention, the second filler added to the raw materials for preparing the in-situ solidified composite solid electrolyte, the micro-nano solid electrolyte filling, on the one hand, acts as a lithium ion fast conductor to provide high ion conductivity; on the other hand, the micro-nano solid electrolyte material forms a close contact with the active material and the polymer electrolyte interface, thereby reducing the impedance of the semi-solid lithium ion battery and improving the performance of the battery; at the same time, the micro-nano solid electrolyte is in close contact with the active material, diffuses on the surface of the active material during the electrochemical reaction to form a protective layer, stabilizes the structure of the active material, and thus improves the cycle performance of the battery.
[0088] In summary, the preparation method of the present invention is simple, and the prepared composite solid electrolyte has the characteristics of good wettability, uniform polymerization reaction, high ion conductivity, etc. when used in lithium-ion batteries, and can improve the stability, rate and cycle performance of semi-solid lithium-ion batteries.
[0089] As described above, the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.
Claims
1. A composite solid electrolyte prepared by using a nanostructured inhibitor adsorption carrier, characterized in that: The raw material components for preparing the composite solid electrolyte include 10-20 parts of small molecule polymer monomers, 1-3 parts of initiators, 2-6 parts of lithium salts, 2-8 parts of fillers, 1-4 parts of inhibitors and 5-10 parts of organic solvents in parts by weight.
2. The composite solid electrolyte prepared by using a nanostructured inhibitor adsorption carrier according to claim 1, characterized in that: The small molecule polymer monomer includes any one of acrylic acid, methacrylic acid, methyl methacrylate, pentaerythritol tetraacrylate, pentaerythritol triacrylate, acrylonitrile, ethylene carbonate, ethylene oxide or 1,3-dioxolane, or a combination of at least two thereof.
3. The composite solid electrolyte prepared by using a nanostructured inhibitor adsorption carrier according to claim 1, characterized in that: The initiator includes any one of azobisisobutyronitrile, azobisisoheptanenitrile, azoisobutylcyanoformamide, dimethyl azobisisobutyrate, dicumyl peroxide or dibenzoyl peroxide, or a combination of at least two thereof.
4. The composite solid electrolyte prepared by using a nanostructured inhibitor adsorption carrier according to claim 1, characterized in that: The lithium salt includes any one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(difluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(oxalato)borate, lithium difluorooxalatoborate or lithium bis(oxalato)borate, or a combination of at least two thereof.
5. The composite solid electrolyte prepared by using a nanostructured inhibitor adsorption carrier according to claim 1, characterized in that: The filler includes a first filler and a second filler, the particle size of the first filler is 10nm-500nm; the first filler includes at least one of Al2O3, TiO2, SiO2, ZrO2, Ta2O5, and La2O3; the particle size of the second filler is 300-1000nm; the second filler includes at least one of Li0.75La0.5TiO3, Li1.3Al0.3Ti1.7(PO4)3, Li7La3Zr2O12, and Li10GeP2S12.
6. The composite solid electrolyte prepared by using a nanostructured inhibitor adsorption carrier according to claim 1, characterized in that: The polymerization inhibitor includes any one of hydroquinone, p-hydroxyanisole, 2,6-di-tert-butyl-p-cresol, 2,5-di-tert-butyl-hydroquinone, 2-tert-butyl-hydroquinone, p-benzoquinone, methyl hydroquinone or tetrachlorobenzoquinone, or a combination of at least two thereof.
7. The composite solid electrolyte prepared by using a nanostructured inhibitor adsorption carrier according to claim 1, characterized in that: The organic solvent includes any one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl formate, dimethoxymethane or acetonitrile, or a combination of at least two thereof.
8. The composite solid electrolyte prepared by using a nanostructured inhibitor adsorption carrier according to claim 1, characterized in that: The raw material for preparing the composite solid electrolyte also includes 2-5 parts of an additive, wherein the additive includes any one of vinylene carbonate, fluoroethylene carbonate, propylene sulfite, ethylene sulfate, fluorobenzene or sodium dodecyl sulfate, or a combination of at least two thereof.
9. A method for preparing a composite solid electrolyte based on a nanostructured inhibitor adsorption carrier, characterized in that: The steps include: A. Firstly, an inorganic nanofiller and a polymerization inhibitor are mixed, and then a polymerization monomer, an initiator, a lithium salt, and an organic solvent are added and mixed to obtain an in-situ solidified electrolyte precursor; B. Then, the in-situ solidified electrolyte precursor is injected into the battery cell, and allowed to stand for 1 minute under a vacuum of -80 kPa. After vacuum packaging, it is allowed to stand for 12-48 hours in an environment of 20-35°C. The pressure during curing is 0.6-3 MPa, and it is cured at 45-80°C for 4-12 hours to obtain an in-situ solidified composite solid electrolyte.
10. The method for preparing a composite solid electrolyte based on a nanostructured inhibitor adsorption carrier according to claim 9, characterized in that: Taking the total mass of the in-situ solidified electrolyte precursor as 100%, the mass percentage of the polymerized monomer is 1%-40%, the mass percentage of the initiator to the mass percentage of the polymerized monomer is 0.01%-3%, the concentration of the lithium salt in the in-situ solidified electrolyte precursor is 1-3 mol / L, the mass percentage of the inhibitor to the mass percentage of the polymerized monomer is 0.0005%-10%, the mass percentage of the organic solvent is 60%-90%; the mass percentage of the additive is 0-10%.